2004
DOI: 10.1016/j.jhsb.2003.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Distal Biceps Tendon Ruptures Using a Suture Anchor and an Anterior Approach

Abstract: In a prospective study, eight consecutive patients with nine ruptures of the distal biceps tendon underwent repair through a single incision. All patients were satisfied with their clinical results and had full ranges of elbow and forearm motion. There were no radial nerve injuries and no radio-ulnar synostoses. Isokinetic testing, after correction for dominance, demonstrated a 6% strength deficit, but 7% higher endurance in the repaired extremity for the flexion-concentric test, and no strength deficit and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 25 publications
(46 reference statements)
1
65
0
6
Order By: Relevance
“…If a free graft is used, we still recommend immobilization for 5 to 6 weeks. Isokinetic testing after acute distal biceps tendon repair showed good recovery of strength and endurance in the repaired extremity for flexion-concentric testing and supination [4]. However, at 1 year followup after the Boyd-Anderson technique, the elbow flexion strength was reduced by 13% and supination strength by 19% [17].…”
Section: Discussionmentioning
confidence: 95%
“…If a free graft is used, we still recommend immobilization for 5 to 6 weeks. Isokinetic testing after acute distal biceps tendon repair showed good recovery of strength and endurance in the repaired extremity for flexion-concentric testing and supination [4]. However, at 1 year followup after the Boyd-Anderson technique, the elbow flexion strength was reduced by 13% and supination strength by 19% [17].…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that surgical repair might be more indicated for athletes, patients with high functional demands and patients who do not accept loss of strength or esthetic deformity (1,4,7) . Surgical repair may attain a muscle strength level similar to that of the unaffected contralateral limb (2,3,6,(8)(9)(10)(11)(12)20) . Studies on surgical treatment have demonstrated high levels of muscle strength and resistance for the elbow flexors and forearm supinators after surgical repair (2,3,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)20) .…”
Section: Methodsmentioning
confidence: 99%
“…The first technique described was lesion repair by means of a single anterior incision. However, reports in the literature have demonstrated complications such as injury to the radial artery, median nerve and posterior interosseous nerve (6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21) . In 1961, Boyd and Anderson (3) introduced a double-incision technique in order to minimize these risks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations